Deteksi Anemia pada Remaja Putri SMA Negeri 4 Kota Lubuklinggau Tahun 2021 - Nadi Aprilyadi; Zuraidah Zuraidah; Bambang Suwito; Wella Juartika (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Anemia is the most common nutritional problem globally, especially in developing countries, which is mainly caused by iron deficiency; WHO data shows that more than 30% or 2.2 billion people worldwide, suffer from anemia (WHO, 2015). Anemia is a condition where the concentration of hemoglobin (Hb) and the red blood cell count is less than 13.5 g/dL in adult men and less than 12 g/dL in adult women. Based on the 2018 Riskesdas data, the prevalence of anemia in adolescents is 32%, meaning that 3-4 out of 10 adolescents suffer from anemia, and the majority of female adolescents who receive blood-supplementing tablets (TTD) at school is 76.2% of the total female adolescents in Indonesia. The purpose of this activity is to increase the knowledge of young women in SMAN 4 with training and counseling in self-detecting anemia through counseling and education activities for 6 months in 2021. The implementation procedure begins through several stages, consisting of registration, weighing, and height, then carried out the Hb examination. Measurement with pre and post-using a questionnaire. The results of the study were 50 students, BMI in SMAN 4 Teenage Girls found that there were 10 (20%) thin teenagers, 12 (24%) girls who had anemia, namely 6 (12%) moderate anemia and 6 (12%). %), Pre-test knowledge, namely young women with good knowledge, 5 (15%). After conducting Health Education about anemia, there were 28 (56%). With this activity, it is hoped that young women can understand the signs and symptoms of anemia and are willing to check and control Hb regularly if anemia occurs, young women can get Fe tablets in health services and consume foods containing Fe and the Simpang Periuk Health Center can periodically check Hb and giving blood-boosting pills to young women at SMAN 4 Lubuklinggau.